Box Cox-Fourier flexible functional forms in stochastic metafrontier analysis : the cost efficiency of the insurance industry in Malaysia - Roziana Baharin,; Zaidi Isa, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Takaful insurance industry is growing rapidly after nearly 30 years of operation. It is therefore desirable for the performance of this industry to be assessed to measure its level of achievement. Since the industry comprises conventional and Takaful insurance industries, then the form of organisation may affect the efficiency. This study used the Meta Stochastic Analysis Parametric Approach in order to measure the relationship between efficiency and organisational structure for family Takaful operators and life insurance operators in Malaysia. The analysis of this study applied the modified Box Cox Fourier functional form for a period of time ranging from 2004 to 2015. The findings showed that there is a significant difference in cost efficiency between the Takaful industry and the life insurance industry. Overall, the Takaful industry has lower cost efficiencies than conventional insurance, proving that the form of organisation has an effect on efficiency. The findings also showed that the average difference in cost efficiency is influenced by technology level gaps.